Malaysian Socio-Technical Disaster Model and Learning System - Mat Said, Aini (2006)

(untitled)
Understanding of the development and causes of the disasters provides a tool for organizational and institutional diagnosis of vulnerability and risks. The hindsight gained from these negative events could be utilized by government and enterprises to design organizational structures that will help reduce the likelihood of disaster as the nation progresses. A multi strategy research was designed utilizing qualitative and quantitative approach to develop a socio-technical disaster model and a learning system for Malaysia. Using a grounded theory approach, six inquiry reports were used to identify the phases associated with the development of the socio-technical disasters and their underlying causes. Management of the inquiry into these disasters and the recommendations made by the tribunal of inquiry were also analyzed. Nvivo software program was utilized to model the latent errors attributed to the disasters. A survey was conducted among Malaysian Disaster experts who were selected using judgmental sampling in order to determine their views on disaster and disaster inquiry management. Data obtained from both qualitative and quantitative study was then transferred into a Visual Basic 6.0 computer program to form a learning and advice model. Despite the differences of disasters involved and their technologies, the disasters were found to exhibit common features and characteristics. The findings demonstrated that socio-technical disasters are not sudden cataclysmic events but they evolved in phases with long developmental period. Underlying causes of the disasters are found to be due to latent errors that are accumulated and get embedded in the system during the incubation period. Inside the organization, a complex set of managerial, procedural, training, safety and failure to learn factors interact with external factors of regulatory and human failures to produce the disasters. The experts were found to have only fair perception towards the management of Public and Royal inquiries into disasters in the country. They were least satisfied with recommendations and learning aspect of the inquiry. This commensurate with the overall perception of the experts that the management of the disaster inquiry should be improved in order to increase learning from them. It was suggested that a flexible guideline should be developed so that it is not entirely left to the personal style of the chairman as currently practiced. The data obtained from the study was further utilized to develop an advice and learning model for public access through an application of an expert system. This is a useful tool for teaching at higher institutions; media of instructions for training institutions and industries; and e- learning for professional development